2018
DOI: 10.5539/mas.v12n3p105
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Organizational Support and Work Adjustment on the Employee Performance of Expatriate Teachers in Thailand

Abstract: This study investigated the influence of perceived organizational support (POS) and work adjustment (WA) on the employee performance (EP) of expatriate English teachers in Thailand. A quantitative method was used; self-evaluation data were collected from 210 expatriate English teachers working in Thailand. The results of the study confirm the hypothesized positive correlational effect of POS and WA on EP. The empirical results confirm the model of investigation consisting of POS, WA and EP developed for testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
3
8
1
Order By: Relevance
“…If the lecturers consider that they received high organizational support, they will integrate organizational membership into their identity and then develop more positive relationships and perceptions of the organization (Rhoades & Eisenberger, 2002). Several previous studies have concluded that organizational support has a positive and significant effect on human resource performance (Arshadi & Hayavi, 2013;Darolia, Kumari, & Darolia, 2010;Mohamed & Ali, 2015;Na-nan, Joungtrakul, & Dhienhirun, 2018). The results of this study are congruent with the results of the previous studies where the elements of help should be considered to be accepted by the lecturer in doing their work.…”
Section: Resultsmentioning
confidence: 99%
“…If the lecturers consider that they received high organizational support, they will integrate organizational membership into their identity and then develop more positive relationships and perceptions of the organization (Rhoades & Eisenberger, 2002). Several previous studies have concluded that organizational support has a positive and significant effect on human resource performance (Arshadi & Hayavi, 2013;Darolia, Kumari, & Darolia, 2010;Mohamed & Ali, 2015;Na-nan, Joungtrakul, & Dhienhirun, 2018). The results of this study are congruent with the results of the previous studies where the elements of help should be considered to be accepted by the lecturer in doing their work.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the calculation of the coefficient of determination for LMX with OCB is about 71.5%. In other words, OCB is influenced by LMX by 71.5%, while the remaining 28.5% is influenced by other factors that are not involved in this study, which can be a transformational leadership [8,27], job satisfaction [28], perceived organizational support (POS) [29], motivation and organizational justice [30].…”
Section: Y = A+ Bxmentioning
confidence: 99%
“…Due to t-count> t table or 4.021> 0.677 then Ha is accepted, this means that LMX has an effect on OCB, with the magnitude of the influence of LMX on OCB by 71.5% and it is categorized in a strong category [25], while the remaining 28.5% is influenced by other factors that are not involved in this study, which can be a transformational leadership [8,27], job satisfaction [28], percieved organizational support (POS) [29], motivation and organizational justice [30].…”
Section: Partial Hypothesis Test (T Test)mentioning
confidence: 99%
“…EWA is an indicator of an employee’s abilities. Different environments impose diverse requirements for successful work relations, and adjustments create a state of correspondence between the individual and the environment to generate high performance (Judge, 1994; Dawis and Lofquist, 1984; Na-Nan, Joungtrakul and Dhienhirun, 2018; Lee et al , 2017; Strauser David and Lustig Daniel, 2011). In addition, EWA is a significant contributing factor to individuals, teams and company success by promoting the ability of employees to adjust which then leads to high effective performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EWA is a vital criterion for employees and teams for optimum output and success (Wahat, 2008). Thus, human resource developers, consultants and individual companies should strive to encourage and improve EWA (Haueter et al , 2003; Firth et al , 2014; Na-Nan, Joungtrakul and Dhienhirun, 2018).…”
Section: Introductionmentioning
confidence: 99%